2018
DOI: 10.1016/j.diabres.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes impairs female fertility even before it is diagnosed

Abstract: Type 1 diabetes compromises female fertility, even before it is diagnosed. Associated hyperthyroidism further reduces fertility. Blood glucose and thyroid function surveillance in infertile females may allow for an early diagnosis of type 1 diabetes and associated thyroid disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…First, T1D prevalence is much lower in China than in Caucasian populations [ 22 ]. Moreover, a nationwide cohort study in Taiwan recently reported that T1D greatly impairs female fertility [ 23 ]. As a result, although all pregnant women with T1D who gave birth between 1 January 2006 and 31 May 2018 were included, the sample size of the study was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…First, T1D prevalence is much lower in China than in Caucasian populations [ 22 ]. Moreover, a nationwide cohort study in Taiwan recently reported that T1D greatly impairs female fertility [ 23 ]. As a result, although all pregnant women with T1D who gave birth between 1 January 2006 and 31 May 2018 were included, the sample size of the study was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…T1DM complicates a relatively small percentage of pregnancies (~1 of 200). Nevertheless, women with T1DM experience fewer livebirths (Lin et al 2018), higher early pregnancy terminations (Sjöberg et al 2017) and a greater risk for preterm births (Ludvigsson et al 2019) than the general population. Increased infiltration and adhesion of monocytes to placental bed endothelium leading to inflammation and reduction of placental blood flow have been suggested to partly underlie these poor birth outcomes in women (Galettis et al 2004) and were mechanistically confirmed in non-obese diabetic mice (Burke et al 2007).…”
Section: Compromised Reproductive Healthmentioning
confidence: 99%
“…Maternal and neonatal morbidity in patients with type 1 diabetes mellitus (T1DM) is well documented, with higher chances of preeclampsia, preterm birth, perinatal mortality, hypoglycemia, retinopathy, hypertension, nephropathy or diabetic ketoacidosis [2,3]. On one hand these patients have reduced rate of pregnancy -partially due to lower fertility [4], but on the other hand the prevalence of T1DM is increasing among the youth [5]. Therefore, the tendency is to increase the number of pregnant with T1DM and obstetricians have to be aware of severe outcomes and complications of these patients.…”
Section: Introductionmentioning
confidence: 99%